(3Yjhf GdCLhHI aj afhf GdCSFdIs - (3YHO GdcQje Hf ghGRf Hf YHO Gdedc GHf WdMI GdfjSGHhQj GdbTjQj, CHh GdbGSe, Rjf GdESdGe,J (B465 (3g` s
(3ChdgG (B:s
(3CeG HYO agPg aUhd SejfGgG Yjhf GdCLhHI ai afhf GdGSFdI eSFdI CMbjbI GdJbhi GdLhGH (B: (3gi GdJMQR HWGYI Gddg Yf YbhHJg s
(3BNQgG (B:s
(3eSFdI eG eYfi GdQhM GdLhGH (B: (3QhM GdGfSGf dWjaI ChOYgG Gddg HOf GdGfSGf ai MGd MjGJg gi eY faSg EfSGf hGMO SNQ Gddg HYVgG dHYV hfYhP HGddg ef GdNPdGf ai GdYbjOI hHGddg GdJhajb hGdMeO ddg QH GdYGdejf s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3HBNQg JNejS dGMOi GdbUGFOs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B57 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B6s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1183s
Keywords: (3Gdabg GdESdGejs